Porcine sperm vitrification II: Spheres method. (10th November 2016) - Arraztoa, C. C.; Miragaya, M. H.; Chaves, M. G.; Trasorras, V. L.; Gambarotta, M. C.; Neild, D. M.
Summary: Owing to current problems in boar sperm cryopreservation, this study proposes to evaluate vitrification in spheres as an alternative cryopreservation procedure, comparing the use or not of permeable cryoprotectants and two warming methods. Extended ( n  = 3; r  = 4) and raw ( n  = 5; r  = 2) porcine spermatozoa were diluted in media, in the absence or presence of either 4% dimethylformamide or 4% glycerol, to a final concentration of 5 × 10 6  spermatozoa/ml and vitrified using the spheres method. Two warming procedures were evaluated: a rapid method (30 s at 37°C) and an ultrarapid method (7 s at 75°C, followed by 30 s at 37°C). Percentages of total motility (phase contrast), membrane function (hypo‐osmotic swelling test), acrosome integrity (phase contrast), sperm viability (6‐carboxyfluorescein diacetate and propidium iodide stain), chromatin condensation (toluidine blue stain) and chromatin susceptibility to acid denaturation (acridine orange stain) were evaluated in the samples before and after vitrification. Results, analysed using Friedman's test, suggest that rapid warming of raw porcine spermatozoa vitrified without permeable cryoprotectants may preserve DNA condensation and integrity better than the other processing methods studied in this work. Hence, porcine sperm vitrification using spheres could be used to produce embryos with ICSI to further validate this method.